2005
DOI: 10.1111/j.1365-3148.2005.00549.x
|View full text |Cite
|
Sign up to set email alerts
|

ABO incompatibility due to immunoglobulin G anti‐B antibodies presenting with severe fetal anaemia

Abstract: ABO incompatibility is a common haematological problem affecting the newborn. The haemolysis is widely accepted to follow a relatively benign course rarely causing the escalating levels of hyperbilirubinaemia and significant anaemia associated with Rh haemolytic disease of the newborn. Case reports of fetal hydrops secondary to ABO incompatibility are particularly rare. We describe two cases, first that of a twin pregnancy with both fetuses developing severe anaemia at 20 weeks gestation, and then a second cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 18 publications
1
24
0
2
Order By: Relevance
“…[3] However, cases in which ABO incompatibility resulted in severe anemia have been described. [5,6] Our study's findings correlate with those of previous works as we found no parameters such as low hematocrit as well as no need for blood transfusions among our cohort of ABO preterm infants with ABO incompatibility, suggesting no indication of significant hemolytic reaction.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[3] However, cases in which ABO incompatibility resulted in severe anemia have been described. [5,6] Our study's findings correlate with those of previous works as we found no parameters such as low hematocrit as well as no need for blood transfusions among our cohort of ABO preterm infants with ABO incompatibility, suggesting no indication of significant hemolytic reaction.…”
Section: Discussionsupporting
confidence: 90%
“…HDN is usually treated successfully with phototherapy alone and rarely requires exchange transfusions, intravenous immunoglobulin (IVIG) administration, or packed red blood cell infusions. However, cases of severe ABO HDN have been described with severe hemolysis and anemia and need for blood transfusions . A previous report involving a large study group of term ABO‐incompatible infants found up to 30% with positive direct antiglobulin test (DAT) (previously termed direct Coombs’ test) and 3.9% clinically significant disease, including the appearance of jaundice, evidence of hemolysis, or both .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In almost all cases of ABO HDFN, the blood type of the mother is group O and that of the child is group A or B. The most common occurs as an anti‐A reaction, but that of the anti‐B reaction can represent a more serious form of hemolytic disorder 12 . The biggest clinical problem of newborns with ABO HDFN is significant premature hyperbilirubinemia 2 and more rarely Ecklin's late anemia.…”
Section: Discussionmentioning
confidence: 99%
“…The most common occurs as an anti-A reaction, but that of the anti-B reaction can represent a more serious form of hemolytic disorder. 12 The biggest clinical problem of newborns with ABO HDFN is significant premature hyperbilirubinemia 2 and more rarely Ecklin's late anemia. Generally, the DAT proves negative; however, it occurs more commonly as a weak positive outcome when carried out on umbilical cord blood.…”
Section: Discussionmentioning
confidence: 99%